eNOS, Cardiac Senescence, and Cardiovascular Aging: A Meta-Analysis of Molecular Mechanisms and Clinical Outcomes - Tri Nisdian Wardiah; Ali Zainal Abidin; Taufik Indrajaya; Nur Riviati (Open Access Indonesian Journal of Medical Reviews, 2024)
Endothelial nitric oxide synthase (eNOS) plays a critical role in maintaining cardiovascular homeostasis. Its dysfunction is implicated in cardiac senescence, a hallmark of aging characterized by cellular decline and increased risk of cardiovascular disease. This meta-analysis investigated the association between eNOS, cardiac senescence, and cardiovascular aging, exploring underlying molecular mechanisms and clinical outcomes. A systematic search of PubMed, Scopus, and Web of Science databases was conducted for relevant studies published between 2013 and 2024. Studies investigating the relationship between eNOS, cardiac senescence markers (e.g., telomere length, p53, p16), and cardiovascular outcomes (e.g., heart failure, myocardial infarction, stroke) were included. Data were extracted and pooled using random-effects models. Nine studies (n=4,875 participants) met the inclusion criteria. Meta-analysis revealed a significant association between reduced eNOS activity and increased cardiac senescence markers (standardized mean difference [SMD] = -0.85; 95% confidence interval [CI], -1.20 to -0.50; p<0.001). Furthermore, eNOS dysfunction was associated with an increased risk of cardiovascular events (relative risk [RR] = 1.62; 95% CI, 1.25 to 2.10; p=0.001). Molecular analysis indicated that eNOS dysfunction contributes to cardiac senescence through increased oxidative stress, inflammation, and impaired autophagy. In conclusion, this meta-analysis provides compelling evidence for the detrimental role of eNOS dysfunction in cardiac senescence and cardiovascular aging. Targeting eNOS may offer promising therapeutic strategies to mitigate age-related cardiovascular decline.